Does chemotherapy increase morbidity and mortality after pneumonectomy? - Alan, Stolz; Jan, Simonek; Tomas, Harustiak; Robert, Lischke; Jan, Schutzner; Pavel, Pafko (Journal of surgical oncology, 2009)
BACKGROUND: The impact of chemotherapy on postoperative complications after pneumonectomy remains unclear, and the procedure is often considered as potentially dangerous. METHODS: This retrospective review of prospectively collected data included 269 patients operated from January 1, 1998 through December 31, 2007. Group 1 included patients those who received preoperative chemotherapy (PCT) and pneumonectomy (54 patients, 20%), and group 2 included patients who underwent pneumonectomy alone (215 patients, 80%). RESULTS: Overall 30- and 90-day mortality rates were 5.9% and 8.9%, respectively. Postoperative mortality at 30 days was 5.6% in group 1 and 6% in group 2 (P = 0.16), and 11.1% for group 1 and 8.3% in group 2 at 90 days (P = 0.8). Incidence of postoperative respiratory failure was 3.7% in group 1 and 3.2% in group 2 (P = 0.62); incidence of empyema was 5.5% in group 1 and 2.8% in group 2 (P = 0.1). Incidence of bronchopleural fistula (BPF) was 3.7% in group 1 and 2.8% in group 2 (P = 0.55); risk of BPF was higher following right pneumonectomy (6.1%) versus left pneumonectomy (0%, P = 0.003). CONCLUSIONS: PCT does not significantly increase postoperative morbidity and early mortality after pneumonectomy in our experience.
Keywords: senioři; pneumektomie; mortalita; Retrospective Studies; Incidence; výsledek terapie; Pneumonectomy; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; nádory plic; incidence; Kaplanův-Meierův odhad; Antineoplastic Agents; Postoperative Complications; Morbidity; morbidita; ženské pohlaví; nemalobuněčný karcinom plic; protinádorové látky; retrospektivní studie; Humans; Mortality; Carcinoma, Non-Small-Cell Lung; lidé středního věku; Female; Aged; Treatment Outcome; Lung Neoplasms; pooperační komplikace; lidé; Male